2015
DOI: 10.1179/1743284714y.0000000735
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nickel and cobalt on microstructure of silicon solution strengthened ductile iron

Abstract: ‘Second Generation’ ductile iron with a silicon content of up to 4.3 wt- exhibits a fully ferritic matrix, which is solution strengthened by silicon. Outstanding advantages of these ductile iron grades result in their strongly increasing demand. However, due to a presumed formation of a silicon long range order, the maximum strength is limited to 600 MPa at 4.3 wt- silicon. At higher silicon content, the mechanical properties dramatically decrease. In order to increase the maximum achievable strength, the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 28 publications
(66 reference statements)
2
16
2
Order By: Relevance
“…Some of the alloys were ferritised by heat-treating at 780°C for 5 h. For comparison purposes only data of fully ferritic structure in the as-cast state are showed in table A2. The works by Fischer et al [22] and Weiss et al [20] were carried out at RWTH-Aachen using the same procedures and indeed report the same results, Weiss et al [20] published the microstructure results and Fischer et al [22] the mechanical properties. The alloys contained 3.8-4.3 wt.% Si and were alloyed with up to 4 wt.% Co.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Some of the alloys were ferritised by heat-treating at 780°C for 5 h. For comparison purposes only data of fully ferritic structure in the as-cast state are showed in table A2. The works by Fischer et al [22] and Weiss et al [20] were carried out at RWTH-Aachen using the same procedures and indeed report the same results, Weiss et al [20] published the microstructure results and Fischer et al [22] the mechanical properties. The alloys contained 3.8-4.3 wt.% Si and were alloyed with up to 4 wt.% Co.…”
Section: Resultsmentioning
confidence: 64%
“…UTS, YS and A values, and Si and Co contents of the alloys investigated byFischer et al and Weiss et al[22,20].…”
mentioning
confidence: 99%
“…These cast iron grades have been defined as "solution strengthened ferritic ductile irons" as they are alloyed with silicon contents in the range 3.2-4.3 wto/o. lt has been reported that such high silicon contents promote high nodule count [1][2][3] and thus favor matrices with very high ferrite fractions. Such alloys have much higher strength than standard ferritic cast irons with comparatively low silicon contents though at the expense of lower ductility.…”
Section: Introductionmentioning
confidence: 99%
“…Lower silicon contents and higher nickel contents are known to promote the nodularity [15]. The lower nodularity of alloy 2 and alloy 3 can therefore only be explained by the addition of aluminum as a ferritizing and solid solution strengthening element.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, it was proven, that cobalt and nickel can be successfully used as additional solid solution strengthening elements in SSF DI [15][16][17]. The mechanical properties of EN-GJS-600-10 were reached at 1.5 wt.% Ni and 3.8 wt.% Si.…”
Section: Introductionmentioning
confidence: 99%